2009
DOI: 10.3109/17482960903278485
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of amyotrophic lateral sclerosis in New Hampshire: A possible role for toxic cyanobacteria blooms

Abstract: Cyanobacteria produce many neurotoxins including beta-methylamino-L-alanine (BMAA) that has been liked to amyotrophic lateral sclerosis (ALS) and neurodegenerative disease. A number of ALS cases have been diagnosed among residents of Enfield, NH, a town encompassing a lake with a history of cyanobacteria algal blooms. To investigate an association between toxic cyanobacterial blooms in New Hampshire and development of ALS, we reviewed records from our institution and other community databases to obtain demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(107 citation statements)
references
References 41 publications
2
104
1
Order By: Relevance
“…Affected waters include those used for drinking water supplies, livestock watering, fishing, crop irrigation and recreation . Human exposure to cyanobacterial blooms and their toxins is potentially widespread and can occur through several routes including accidental and/or incidental dermal contact, ingestion and inhalation during recreational and occupational activities (Pilotto et al, 2004;Stewart et al, 2006;Caller et al, 2009) and through the consumption of ineffectively-treated drinking water (Falconer et al, 1983), shellfish and finfish (Falconer et al, 1992) and spray-irrigated crops (Codd et al, 1999;Crush et al, 2008).…”
Section: Cyanobacteria and Human Healthmentioning
confidence: 99%
“…Affected waters include those used for drinking water supplies, livestock watering, fishing, crop irrigation and recreation . Human exposure to cyanobacterial blooms and their toxins is potentially widespread and can occur through several routes including accidental and/or incidental dermal contact, ingestion and inhalation during recreational and occupational activities (Pilotto et al, 2004;Stewart et al, 2006;Caller et al, 2009) and through the consumption of ineffectively-treated drinking water (Falconer et al, 1983), shellfish and finfish (Falconer et al, 1992) and spray-irrigated crops (Codd et al, 1999;Crush et al, 2008).…”
Section: Cyanobacteria and Human Healthmentioning
confidence: 99%
“…Aerosols can arise for example through wave action, splashing, boating, showering, water hose mists, humidifier use as well as bubble formation (Schlichting, 1974) and exposure to biofilms in cooling towers (Hauer, Capek, & Bohmova, 2015). Caller et al (2009) reported higher ALS incidence for residents within 0.5 mile of, and especially downwind of, eutrophic New Hampshire lakes; similarly Bradley et al (2013) postulated that degree of ALS risk may be related to distance from water bodies which harbor cyanobacterial blooms. Such observations have implications for lakefront communities and cottage owners, as well as commercial fishers.…”
Section: Discussionmentioning
confidence: 99%
“…In fish this toxin increases with age (Lage et al, 2015), and carnivorous, filter-feeding and some omnivorous species are associated with the greatest biomagnifications, as are bottom feeding species (Jiao et al, 2014). A number of workers (Caller et al,2009(Caller et al, , 2012Bradley et al, 2013) have reviewed the putative links between regions subject to cyanobacterial blooms, for example proximity to lakes, agricultural lagoons or consumption of local fish, and clusters of ALS occurrence in the human population. Lake Winnipeg, the 10 th largest freshwater lake in the world, is of great importance for recreation, tourism, commercial and sport fisheries, and provides drinking water for several communities and many point-source users.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the findings reported above, research on the spatial distribution features of ALS incidence is scarce. The analysis of geographical patterns such as pollution (Caller et al, 2009;CaparrosLefebvre et al, 2006) and sunlight-deprivation (Sato et al, 1997) provide possible clues for the cause of ALS but no hard facts. Some studies employed spatial analysis techniques to examine spatial clusters of ALS but they only attempted to identify the geographical disparities in its distribution and did not offer any clear association with environmental factors (Caller et al, 2012).…”
Section: Introductionmentioning
confidence: 99%